Automated numerical framework for vibration damping and isolation systems in Ukraine's infrastructure reconstruction - Moiseienko, Dmytro (National Technical University "Kharkiv Polytechnic Institute", 2025)
This research addresses the urgent need for resilient infrastructure in Ukraine by developing an automated numerical framework to optimize vibration damping and isolation systems. Combining finite element analysis (FEM) with machine learning algorithms, the study enables precise simulation of quasi-static and dynami behavior while streamlining parameter selection. The resulting methodology and solution database aim to enhance construction safety, reduce costs, and accelerate post-war reconstruction.
Keywords: vibration isolation; finite element method; infrastructure resilience; automated design; dynamic analysis; Ukraine reconstruction